Serum Biomarkers of Inflammation, Fibrosis, and Cardiac Function in Facilitating Diagnosis, Prognosis, and Treatment of Anti-SSA/Ro–Associated Cardiac Neonatal Lupus - Saxena, Amit (J Am Coll Cardiol, 2015)
BACKGROUND: Cardiac manifestations of neonatal lupus (cardiac NL) include congenital heart block and cardiomyopathy. Several candidate biomarkers were evaluated in cases at risk for cardiac NL on the basis of potential roles in inflammation, fibrosis, and cardiac dysfunction: C-reactive protein (CRP); NT-pro-B-type natriuretic peptide (NT-proBNP); troponin I; matrix metalloproteinase (MMP)-2; urokinase plasminogen activator (uPA); urokinase plasminogen activator receptor (uPAR); plasminogen; and vitamin D. OBJECTIVES: Identification of maternal and fetal biomarkers associated with development and morbidity of cardiac NL should provide clues to pathogenesis with translational implications for management. METHODS: Cord and maternal blood samples (139 each) collected during pregnancies at risk for cardiac NL were available for study. Levels of cord and maternal CRP, cord NT-proBNP, and cord troponin I were evaluated using multiplex assays. Cord and maternal vitamin D were assessed by liquid chromatography-mass spectrometry. MMP-2, uPA, uPAR, and plasminogen were evaluated using ELISA. RESULTS: Cord CRP, NT-proBNP, MMP-2, uPA, uPAR, and plasminogen levels were higher in cardiac NL-affected fetuses than in unaffected cases, independent of maternal rheumatic disease, season at highest risk of cardiac NL development, and medications taken during pregnancy. These biomarkers were positively associated with a disease severity score derived from known risk factors for mortality in cardiac NL. Maternal CRP and cord troponin I levels did not differ between the groups. Cord and maternal vitamin D levels were not significantly associated with cardiac NL, but average maternal vitamin D level during pregnancy was positively associated with longer time to postnatal pacemaker placement. CONCLUSIONS: These data support the association of fetal reactive inflammatory and fibrotic components with development and morbidity of cardiac NL. Following CRP and NT-proBNP levels after birth can potentially monitor severity and progression of cardiac NL. MMP-2 and the uPA/uPAR/plasminogen cascade provide therapeutic targets to decrease fibrosis. Although decreased vitamin D did not confer increased risk, given the positive influence on postnatal outcomes, maternal levels should be optimized.